Levels of anti-M2 and anti-β1 autoantibodies do not correlate with the degree of heart dysfunction in Chagas' heart disease - Talvani, Andre (2006)
Chronic chagasic cardiomyopathy (CCC) is characterized mainly by a dilated cardiomyopathy complicated by frequent and complex ventricular arrhythmias and/or conduction defects. The aim of the present study was to evaluate functional implications of neurotransmitter receptor autoantibodies in vivo. Sera from chagasic patients were used to measure the level of autoantibodies to peptide fragments from the M2 cholinergic and β1 adrenergic receptors. Optical density values and the frequency of anti-M2 and anti-β1 antibodies were significantly higher in the indeterminate form and in CCC patients than in normal individuals. There was no correlation between levels of autoantibodies and clinical parameters of ventricular dysfunction, as assessed by echocardiography. Patients presenting with chronotropic insufficiency in exercise test had higher levels of anti-M2 but not anti-β1 autoantibodies. Although anti-M2 and anti-β1 antibodies do not appear to play a role in the pathophysiology of the heart failure that accompanies severe CCC, anti-M2 cholinergic autoantibodies may contribute to the pathogenesis of Chagas' disease dysautonomia.